ANALISIS PENGARUH SISTEM INFORMASI AKUNTANSI MANAJEMEN DAN PENGUKURAN KINERJA TERHADAP KINERJA MANAJERIAL PT. PUPUK KALTIM - Ramadhini, Putri Aulia; Kusumah, Angga; Achmad, Andi; Gunawan, Candra; Suyudi, Muhammad (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2025)
This research aims to determine the influence of the Management Accounting Information System and Performance Measurement System on Managerial Performance at PT Pupuk Kalimantan Timur Tbk. This research uses a quantitative approach, using primary data through questionnaires. The respondents in this research were the Business and Administration Department at PT Pupuk Kalimantan Timur. The independent variable used in this research is Managerial Performance. In this research, the analytical tool used is multiple linear regression. The research results show that the management accounting information system and performance measurement system have a positive and significant effect on managerial performance. So it can be concluded that H1 and H2 are accepted. The research results also show that the management accounting information system and performance measurement system simultaneously have a positive and significant influence on managerial performance at PT Pupuk Kalimantan Timur Tbk